Derecho e Inteligencia Artificial en el mundo de hoy: escenarios internacionales y los desafíos que representan para el Perú - Valero Quispe, Christian Dennis (2021)
There is a tendency to digitalize human activities, as evidenced by computers and the internet. In addition to this trend, there are intelligent machines capable of simulating human behavior known as artificial intelligence, whose development has caused a radical change in the application of the different branches of knowledge, including Law.In this article, the author analyzes the irruption of intelligent systems developed in the field of Law at a national and international level, and also raises the main challenges they represent for the legal world. In addition, he argues that the mechanical part of Law will be carried out by machines, and the practical part by people; in view of which, it is no longer enough to be trained only in legal issues, it is now necessary to be trained also in technology issues, and to give greater emphasis to the subjects of argumentation and litigation. In this way, the author concludes that judges of first instance will probably be replaced by robots, but for the higher instances the decision-makers will be people (by virtue of the ideal of justice).